Carbon-based catalyst as well as preparation method and application thereof
By adding vulcanization treatment during the preparation of carbon-based catalysts, new sulfate species are generated, the problem of secondary pollution during dioxin regeneration is solved, the oxidation activity of the catalyst and the regeneration conversion rate of dioxin are improved, and the Secondary pollution.
Patent Information
- Application Number
- CN202411531357.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art has the risk of secondary release of pollutants during the regeneration of dioxins, and dioxins cannot be effectively decomposed under an oxygen-depleted environment, resulting in high-temperature desorption and releasing them into the air again, causing secondary pollution.
Using carbon-based catalyst, by adding vulcanization treatment during the preparation process, a new sulfate species X2O3(SO4)2 is generated on the surface of the catalyst, which improves the oxidation activity of the catalyst and enhances the dioxin oxidation and degradation ability in oxygen-poor environments, thereby Improve the regeneration conversion rate of dioxin.
The regeneration conversion rate of dioxin is significantly improved, its regeneration and release amount is reduced, secondary pollution is reduced, the oxidation activity of the catalyst is improved, and the redox cycle in an oxygen-poor environment is enhanced.
Smart Images

Figure CN119236974A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic combustion environmental protection, and specifically relates to a carbon-based catalyst and a preparation method and application thereof. Background Art
[0002] In recent years, in order to comprehensively strengthen ecological environmental protection and win the battle to protect the blue sky, a number of measures have been taken to significantly improve the scientificity, pertinence and effectiveness of volatile organic compounds (VOCs) governance. Among them, dioxins, as the most toxic and chemically stable organic pollutants known to date, are extremely carcinogenic, teratogenic and bioaccumulative, causing serious harm to human health and their living environment, and have become the difficulty and focus of VOCs prevention and control. According to statistics, in 2018, dioxin emissions from metal production accounted for 53.72% of total emissions. Flue gas emitted from steel sintering is the largest source of dioxins. How to effectively control it is a problem that needs to be solved urgently to achieve ultra-low emissions of flue gas in the steel industry.
[0003] At present, the main methods for controlling dioxin emissions include catalytic oxidation and activated carbon adsorption. Among them, the activated coke / carbon dry integrated removal process is one of the most effective methods for the simultaneous removal of multiple pollutants such as NOx, SO2, Hg and dioxins in sintering flue gas because of its advantages of low removal temperature, no water consumption, resource utilization of pollutants and simultaneous removal of multiple pollutants. The process mainly includes two units: adsorption removal and desorption regeneration. In the adsorption tower, SO2 is adsorbed and converted into H2SO4 and stored in the activated coke pores. VOCs such as dioxins and heavy metals such as Hg are also adsorbed on the activated coke at the same time. NOx is converted into N2 through SCR. The activated coke after adsorption of pollutants is transported to the desorption regeneration tower for heating and regeneration. In the regeneration tower, the released SO2 can be used to prepare sulfuric acid and sulfur, etc., to achieve its resource utilization, and the activated coke after desorption and regeneration can be recycled. The regeneration process can effectively restore the activity of the activated coke / carbon catalyst, but under high temperature conditions, pollutants such as SO2 and dioxins may be directly desorbed and released, causing secondary pollution.
[0004] The existing technology mainly focuses on the development of catalysts for the catalytic oxidation of dioxins under oxygen-rich conditions in the reaction unit, but lacks attention to the control of dioxins in the regeneration process and the development of catalysts, which poses a risk of secondary release of pollutants. Therefore, it is of great significance to develop a catalyst that improves the conversion rate of dioxins in the regeneration process.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a carbon-based catalyst for improving the dioxin regeneration conversion rate and a preparation method thereof, so as to solve the above problems.
[0007] In order to achieve the above objectives, the present invention particularly adopts the following technical solutions:
[0008] The present invention provides a carbon-based catalyst, which comprises a carrier and an active component. The carrier comprises one or more of activated carbon, carbon nanotubes and activated coke, and the active component comprises a sulfide transition metal salt.
[0009] Preferably, the precursor of the active component is one or more of metavanadate, manganese acetate and cerium nitrate, and the mass ratio of the active component to the carrier is 4-6%;
[0010] Preferably, the sulfide transition metal salt includes one or more of sulfide vanadates, sulfide manganates and sulfide cerates.
[0011] The present invention provides a method for preparing the carbon-based catalyst, comprising the following steps:
[0012] (1) Pretreatment: treating the carrier with acid and drying it to obtain an acid-treated carrier; dissolving the active component precursor and the acid solution into solution A, stirring and heating the solution A; dissolving the acid-treated carrier into solution A by an equal volume impregnation method, and drying it to obtain a catalyst precursor.
[0013] (2) Heat treatment: calcining the catalyst precursor obtained in step (1) to obtain a transition metal carbon catalyst.
[0014] (3) Sulfurization treatment: The transition metal carbon catalyst obtained in step (2) is subjected to desulfurization treatment to obtain a carbon-based catalyst containing a sulfided transition metal salt.
[0015] 4. The method for preparing a carbon-based catalyst according to claim 3, characterized in that the acid treatment conditions in step (1) are to use 6-8 mol / L HCl and HF at 60°C-80°C for 6-8h respectively;
[0016] The acid solution is oxalic acid and / or acetic acid;
[0017] During the preparation of solution A, the solution was stirred at a speed of 50-80 r / min and heated at 50°C-70°C, and the solution changed from yellow-green to dark blue.
[0018] Preferably, the ultrasonic treatment in step (1) is carried out under the conditions of an ultrasonic frequency of 40-60 KHz, a temperature of 50-60° C., and a treatment time of 2-2.5 h;
[0019] The ratio of solution A to acid-treated support solid was 1:1.
[0020] Preferably, in step (1), the carrier is treated with acid, the drying temperature is 110-120° C., and the drying time is 24-36 h;
[0021] The acid-treated carrier is dissolved in solution A by an equal volume impregnation method. The drying conditions are: first drying at room temperature for 5-8 hours, and then drying in a forced air drying oven at 110-120° C. for 24-36 hours.
[0022] Preferably, in step (2), the calcination is carried out in an inert atmosphere and an air atmosphere, respectively, at a calcination temperature of 450-550° C. and a calcination time of 4-6 h; the calcination temperature in air is 240-260° C. and the calcination time in air is 4-6 h;
[0023] Preferably, the inert atmosphere is N2 or Ar.
[0024] Preferably, step (3) simulates flue gas removal conditions in a fixed bed reactor to perform desulfurization treatment;
[0025] Preferably, the sulfidation conditions are: temperature of 110-130° C., gas flow rate of 180-220 mL / min, containing 800-1000 ppm SO2, 0-5 vol% H2O, 8-12 vol% O2, and N2 / Ar as the balance gas.
[0026] The present invention provides an application of the carbon-based catalyst, wherein the carbon-based catalyst is applied to the removal and regeneration of dioxins.
[0027] Preferably, the carbon-based catalyst after dioxin removal is regenerated at 400-500° C. in an inert atmosphere for 1-2 hours at a heating rate of 5-10° C. / min.
[0028] Beneficial effects of the present invention:
[0029] During the regeneration process of the carbon-based dry process integration, in an oxygen-deficient environment, the adsorbed dioxins cannot be effectively decomposed, and are desorbed at high temperature and released into the air again, causing secondary pollution. The present invention generates new sulfate species X2O3(SO4)2 on the catalyst surface by adding a sulfurization treatment operation during the catalyst preparation process, wherein X (X = V, Mn, Ce) is a transition metal, and compared with the traditional active component transition metal oxide, its structure has more active oxygen species, which can increase lattice oxygen for the oxidative degradation of dioxins in an oxygen-deficient environment, accelerate the redox cycle, thereby improving the oxidation activity of the catalyst, and ultimately improving the regeneration conversion rate of dioxins in the regeneration process and reducing their regeneration release amount. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0031] Figure 1 is the dioxin regeneration conversion rate of the catalyst;
[0032] Figure 2(a) is the Raman analysis of the catalyst-I D / I G Figure; Figure 2 (b) is a Raman analysis of the catalyst - V species analysis;
[0033] Figure 3 is the electron paramagnetic resonance (EPR) pattern of the catalyst;
[0034] Figure 4(a) is a V2p peak diagram; Figure 4(b) is an O1s peak diagram; Figure 4(c) is an S2p peak diagram;
[0035] FIG5(a) is a product tail gas analysis diagram of the catalyst; FIG5(b) is a product catalyst surface analysis diagram of the catalyst;
[0036] Figure 6 These are the transition state decomposition diagrams of dibenzofuran on V2O5 / AC and V2O3(SO4)2 / AC respectively. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0038] Unless defined otherwise, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs, and the disclosure and materials cited therein are hereby incorporated by reference.
[0039] Technical equivalents to the specific embodiments described that are apparent to those skilled in the art using no more than routine experimentation are intended to be encompassed by this application.
[0040] The experimental methods in the following examples are all conventional methods unless otherwise specified. The instruments and equipment used in the following examples are all conventional laboratory instruments and equipment unless otherwise specified; the experimental materials used in the following examples are all purchased from conventional biochemical reagent stores unless otherwise specified.
[0041] Embodiment 1:
[0042] Commercial activated coke was crushed and sieved to obtain activated coke particles of 40-60 mesh. The activated coke particles were treated with 6 mol / L HF and HCl at 60°C for 8 h respectively. The activated coke particles were then washed with deionized water until the upper clear liquid was neutral and dried in a forced air drying oven at 110°C overnight.
[0043] Vanadium-carbon catalyst (V / AC) was prepared by equal volume impregnation method. NH4VO3 and H2C2O4·2H2O were dissolved in deionized water respectively. During the preparation of the solution, the solution was stirred at a speed of 80r / min and heated at 60℃. The solution changed from yellow-green to dark blue to obtain an impregnation solution. The activated coke after acid washing was dissolved in the above impregnation solution at a ratio of solid to liquid of 1:1, and ultrasonically treated for 2h at an ultrasonic frequency of 40KHz and a temperature of 60℃. Then the above solution was dried at room temperature for 7h and at 110℃ in a blast drying oven for 30h. Subsequently, the obtained solid was calcined in a N2 atmosphere at 500℃ in a tube furnace and a muffle furnace and pre-oxidized in air at 250℃ for 5h to obtain V / AC.
[0044] The catalyst was sulfided in a fixed bed reactor under the following sulfidation conditions: temperature of 120°C, gas flow rate of 200 mL / min, containing 1000 ppm SO2, 10 vol% O2, and N2 as the balance gas, to obtain a sulfided catalyst V / AC-S.
[0045] The obtained catalyst was used for dioxin removal and regeneration: the catalyst after dioxin removal was regenerated at 450℃ in N2 atmosphere for 1.5h, with a heating rate of 5℃ / min. The dioxins in the tail gas were collected by ethanol and detected by GCMS, and the regeneration conversion rate of dioxins was calculated. Among them, 71.24% of the dioxins were directly desorbed from the catalyst surface, and the regeneration conversion rate of dioxins was 28.76%. Figure 1 shown.
[0046] Embodiment 2:
[0047] Example 2 is basically the same as Example 1, except that the conditions for the sulfidation treatment in the fixed bed reactor are: temperature of 120° C., gas flow rate of 200 mL / min, containing 1000 ppm SO2, 5 vol% H2O, 10 vol% O2, and N2 as the balance gas, to obtain the sulfided catalyst V / AC-SH.
[0048] The obtained catalyst was applied to the removal and regeneration of dioxins: the catalyst after dioxin removal was regenerated at 400°C in N2 atmosphere for 1.5 hours, with a heating rate of 5°C / min. The dioxins in the tail gas were collected by ethanol and detected by GCMS, and the regeneration conversion rate of dioxins was calculated, of which 51.95% of the dioxins were directly desorbed from the catalyst surface, and the regeneration conversion rate of dioxins was 48.05%.
[0049] In the regeneration process of the active coke dry process, the adsorbed dioxins cannot be effectively decomposed in an oxygen-deficient environment, and are desorbed and released into the air again at high temperature, causing secondary pollution. The present invention adds a sulfurization treatment operation during the catalyst preparation process to generate a new sulfate species V2O3(SO4)2 on the catalyst surface. Compared with the traditional active component V2O5, its structure has more active oxygen species, which can increase the lattice oxygen and accelerate the V2O3(SO4)2 oxidation degradation of dioxins in an oxygen-deficient environment. 4+ →V 5+ circulation, thereby improving the oxidation activity of the catalyst, and ultimately increasing the regeneration conversion rate of dioxins during the regeneration process and reducing their regeneration release.
[0050] Comparative Example 1:
[0051] The V / AC catalyst prepared in Example 1 was directly subjected to dioxin removal without sulfidation treatment, and then the catalyst was regenerated at 450°C in a N2 atmosphere for 1.5 h at a heating rate of 5°C / min. The dioxin desorption rate in this process was 79.12%, and the dioxin regeneration conversion rate was 20.88%.
[0052] It can be seen from Example 2 and Comparative Example 1 that the carbon-based catalyst of the present invention can significantly improve the regeneration conversion rate of dioxins after sulfurization treatment, and the conversion rate is as high as 48.05%, which is about 2.5 times that of the unsulfurized catalyst, effectively realizing the efficient degradation of dioxins during the regeneration process, and there are fewer degradation by-products both in the gas phase and on the catalyst surface during the regeneration process, thereby reducing the direct release of dioxins and secondary pollution.
[0053] The physicochemical properties of the vanadium-carbon catalyst and the decomposition products of dioxins during the regeneration process were analyzed, and the degradation process of dioxins on the carbon-based catalyst was simulated by theoretical calculation.
[0054] Figure 2 is a Raman analysis of the catalyst. Two sharp peaks are observed in Figure 2(a). -1 The peak at is the graphite (G) band, which is due to the sp 2 The stretching vibration of hybrid carbon on the graphite plane is caused by the -1 The nearby peaks belong to the disorder (D) band, which is caused by the defects of disordered carbon. D / I G It is a classic parameter for evaluating the catalytic activity of catalysts. D / I G The enhancement of shows that the presulfided catalyst has more defects and a higher degree of amorphism, which indicates that the sulfided catalyst has more active sites than the unsulfided catalyst, thereby improving its catalytic activity. In addition, Raman spectroscopy was used to analyze the presence and formation of vanadium species on the sulfided catalyst, and the results are shown in Figure 2(b). Compared with V / AC, some new peaks appeared on the presulfided catalyst. 1011cm -1 The band at 535cm is attributed to the characteristic peak of ν (V=O) -1 The characteristic peak at 449 cm is ν(SOV), which comes from V2O3(SO4)2. -1 The characteristic peak at is ν(SO4 2- The appearance of ν(V=O) and ν(SOV) characteristic vibrations provides strong evidence for the conversion of V2O5 into V2O3(SO4)2 after presulfidation.
[0055] Figure 3 This is the electron paramagnetic resonance (EPR) spectrum of the catalyst. The distribution of oxygen vacancies and defect structures on the catalyst was analyzed using the EPR spectrum. Obviously, Figure 3 A strong signal with a g value of 2.003 was observed for all catalysts, which was attributed to the oxygen vacancy peak. This indicates that a large number of oxygen vacancies exist in all catalysts. After sulfurization treatment, the signal intensity gradually increased, which strongly proves that the introduction of sulfur species is the cause of the increase in oxygen vacancies. This is consistent with the results of Raman analysis. In fact, abundant oxygen vacancies are conducive to the adsorption and activation of oxygen, as well as the migration of oxygen, thereby accelerating the redox cycle and promoting excellent catalytic performance.
[0056] Figure 4 shows the X-ray photoelectron spectroscopy (XPS) analysis of the catalyst. XPS was used to further analyze the surface properties of the catalyst. The XPS spectra of V2p, O1s and S2p were analyzed separately, as shown in Figure 4. Figure 4(a) shows the peak analysis of V2p, and the peak at 516.5 eV is V 4+ , 517.3eV is V 5+ , V 5+ / (V 5+ +V 4+The relative content of ) increased from 75.38% on the V / AC catalyst to 87.45% on the V / AC-SH catalyst. The high-valent vanadium content on the catalyst increased after surface sulfidation, which was beneficial to the oxidative decomposition of dibenzofuran. The XPS spectrum curve of O1s in Figure 4(b) was fitted into three peaks: the peak of 530.4 eV belongs to the lattice oxygen O 2- (O β ), the peak at 532.1 eV belongs to the surface adsorbed O 2- , O - , or O2 2- (O α ), the peak at 533.7 eV belongs to adsorbed water (O γ ) in the acidic free radical or -OH. β The relative content of O increased from 20.48% in V / AC to 35.19% in V / AC-SH, which indicates that more lattice oxygen was generated on the surface after sulfurization. β O has a high reactivity and dominates the oxidation reaction, so O β The increase in may also mean that the sulfided catalyst has better oxidation performance. The deconvolution spectrum of S2p in Figure 4(c) contains four characteristic peaks. The peaks 165.3 and 163.8 eV are from (-CSC) thiophene sulfur, 168.4 eV is attributed to sulfite (SO3 2- ), and 170.8 eV for sulfate (SO4 2- ). It is worth noting that SO3 on the sulfided catalyst 2- The content increased to 59.16%, which is about 3 times that of V / AC. 2- The content of also increased from 13.78% to 29.93%, which indicated that more sulfites and sulfates were formed during the sulfidation process, which also indicated the generation of sulfidation catalyst.
[0057] Figure 5 shows the product analysis of the catalyst (Figure 5 (a) tail gas and Figure 5 (b) catalyst surface). The gas phase products during the regeneration process and the products remaining on the catalyst were analyzed by GC-MS. As can be seen from Figure 5, compared with V / AC, fewer by-products were detected in the gas and catalyst surface of the sulfided catalyst, indicating that deeper oxidation occurred on the catalyst after sulfidation, which further illustrates that the sulfided catalyst is beneficial to the regeneration and conversion of dibenzofuran.
[0058] Figure 6 The transition state decomposition diagrams of dibenzofuran on V2O5 / AC and V2O3(SO4)2 / AC are shown in Figure 2. The decomposition process of dibenzofuran on V / AC and sulfide catalyst VS / AC was simulated using material studio. Figure 6It can be seen that for V / AC, DBF is adsorbed on the catalyst surface through O atoms, and the adsorption energy is -1.00eV. The CH bond on the benzene ring is oxidized by lattice oxygen to form dibenzofuran alcohol, and the reaction energy barrier is 3.64eV. Subsequently, dibenzofuran alcohol undergoes a ring-opening reaction, and CO is continuously removed at an energy barrier of 3.77eV to be converted into ethynylbenzofuran. The CC bond is further activated to form benzofuran, and the reaction is an energy barrier of 8.97eV, which is the rate-determining step for the decomposition of dibenzofuran. Similar to V / AC, the CH bond oxidation and CC bond cleavage of DBF on VS / AC to form benzofuran, the reaction energy barriers are 3.09eV and 4.42eV, respectively. It is worth noting that the reaction energy barrier for the degradation of dibenzofuran on VS / AC is always much lower than that on V / AC, especially the rate-determining step of CC bond cleavage drops significantly from 8.97eV to 4.42eV. This may be due to the fact that during the oxygen-poor regeneration process, SO4 2- The abundant oxygen atoms in the catalyst can deeply participate in the reaction and immediately supplement the oxygen vacancies to oxidize dibenzofuran, which strongly proves that the sulfurized catalyst is beneficial to the decomposition of dibenzofuran.
[0059] Comparative Example 2:
[0060] Comparative Example 2 is basically the same as Comparative Example 1, except that the catalyst was regenerated at 400°C, N2 atmosphere, for 1.5 hours at a heating rate of 5°C / min. The dioxin desorption rate was 85.10% and the dioxin regeneration conversion rate was 14.90%.
[0061] Comparative Example 3:
[0062] Comparative Example 3 is basically the same as Comparative Example 1, except that the catalyst was regenerated at 500°C, N2 atmosphere, for 1.5 hours, with a heating rate of 5°C / min. The dioxin desorption rate was 76.90%, and the dioxin regeneration conversion rate was 23.10%.
[0063] Embodiment 3:
[0064] Example 3 is basically the same as Example 1, except that: the transition metal precursor is Mn(CH3COO)2·4H2O, Mn(CH3COO)2·4H2O and H2C2O4·2H2O are dissolved in deionized water respectively, and during the preparation of the solution, the solution is stirred at a speed of 60r / min and heated at 55°C to obtain an impregnation solution. The activated coke after pickling is dissolved in the obtained impregnation solution at a ratio of solid to liquid of 1:1, and then subjected to the same ultrasonication, drying and high-temperature calcination as in Example 1 to obtain Mn / AC.
[0065] The conditions for sulfidation treatment in a fixed bed reactor are: temperature of 110°C, gas flow rate of 220 mL / min, containing 900 ppm SO2, 3 vol% H2O, 12 vol% O2, and N2 as the balance gas, to obtain the sulfided catalyst Mn / AC-SH.
[0066] The obtained catalyst was applied to the removal and regeneration of dioxins: the catalyst after dioxin removal was regenerated at 500°C in N2 atmosphere for 1 hour, with a heating rate of 8°C / min. The dioxins in the tail gas were collected by ethanol and detected by GCMS, and the regeneration conversion rate of dioxins was calculated, of which 68.74% of the dioxins were directly desorbed from the catalyst surface, and the regeneration conversion rate of dioxins was 31.26%.
[0067] Embodiment 4:
[0068] Example 3 is basically the same as Example 1, except that: the transition metal precursor is Ce(NO3)2·6H2O, Ce(NO3)2·6H2O and H2C2O4·2H2O are dissolved in deionized water respectively, and after stirring and heating in the same way as in Example 1, an impregnation solution is obtained. The activated coke after pickling is dissolved in the obtained impregnation solution at a ratio of solid to liquid of 1:1, and then after ultrasonication, drying and high-temperature calcination in the same way as in Example 1, Mn / AC is obtained.
[0069] The conditions for sulfidation treatment in a fixed bed reactor are: temperature of 130°C, gas flow rate of 200 mL / min, containing 1000 ppm SO2, 4 vol% H2O, 12 vol% O2, and N2 as the balance gas, to obtain the sulfided catalyst Ce / AC-SH.
[0070] The obtained catalyst was applied to the removal and regeneration of dioxins: the catalyst after dioxin removal was regenerated at 450°C in N2 atmosphere for 2 hours, with a heating rate of 6°C / min. The dioxins in the tail gas were collected by ethanol and detected by GCMS, and the regeneration conversion rate of dioxins was calculated, of which 66.55% of the dioxins were directly desorbed from the catalyst surface, and the regeneration conversion rate of dioxins was 33.45%.
[0071] The carbon-based catalyst of the present invention is prepared by impregnation of a carrier and an active component transition metal precursor, and after high-temperature heat treatment, different degrees of presulfurization treatment are performed in a fixed bed reactor to obtain a carbon-based catalyst containing different transition metal sulfide salt contents. The obtained catalyst has a large specific surface area, a simple preparation method, and low cost, and can significantly reduce the secondary release of dioxins and the generation of toxic byproducts during the regeneration process of the carbon-based dry integrated removal process.
[0072] Please note that the technical features of the above embodiments can be combined arbitrarily. In order to make the description concise, all possible combinations of the technical features in the above embodiments are not described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification. The above embodiments only express several implementation methods of the present application, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, without departing from the concept of the present application, several variations and improvements can be made, which all belong to the scope of protection of the present application. Therefore, the scope of protection of the patent in this application shall be based on the attached claims.
Claims
1. A carbon-based catalyst, characterized in that The carbon-based catalyst comprises a carrier and an active component, wherein the carrier comprises one or more of activated carbon, carbon nanotubes and activated coke, and the active component comprises a sulfide transition metal salt.
2. The carbon-based catalyst according to claim 1, characterized in that The precursor of the active component is one or more of metavanadate, manganese acetate and cerium nitrate, and the mass ratio of the active component to the carrier is 4-6%; Preferably, the sulfide transition metal salt includes one or more of sulfide vanadates, sulfide manganates and sulfide cerates.
3. A method for preparing the carbon-based catalyst according to claim 1 or 2, comprising the following steps: (1) Pretreatment: treating the carrier with an acid, and drying to obtain an acid-treated carrier; dissolving the active component precursor and the acid solution into a solution A, stirring and heating during the preparation of the solution A; dissolving the acid-treated carrier in the solution A by an equal volume impregnation method, and drying to obtain a catalyst precursor; (2) heat treatment: calcining the catalyst precursor obtained in step (1) to obtain a transition metal carbon catalyst; (3) Sulfurization treatment: The transition metal carbon catalyst obtained in step (2) is subjected to desulfurization treatment to obtain a carbon-based catalyst containing a sulfided transition metal salt.
4. The method for preparing a carbon-based catalyst according to claim 3, characterized in that: The acid treatment conditions of step (1) are: 6-8 mol / L HCl and HF at 60°C-80°C for 6-8h respectively; The acid solution is oxalic acid and / or acetic acid; During the preparation of solution A, the solution was stirred at a speed of 50-80 r / min and heated at 50°C-70°C, and the solution changed from yellow-green to dark blue.
5. The method for preparing a carbon-based catalyst according to claim 3, characterized in that: The ultrasonic treatment conditions in step (1) are as follows: the ultrasonic frequency is 40-60 KHz, the temperature is 50-60° C., and the treatment time is 2-2.5 h; The ratio of solution A to acid-treated support solid was 1:
1.
6. The method for preparing the carbon-based catalyst according to claim 3, characterized in that: In step (1), the carrier is treated with acid, the drying temperature is 110-120° C., and the drying time is 24-36 hours; The acid-treated carrier is dissolved in solution A by an equal volume impregnation method. The drying conditions are: first drying at room temperature for 5-8 hours, and then drying in a forced air drying oven at 110-120° C. for 24-36 hours.
7. The method for preparing a carbon-based catalyst according to claim 3, characterized in that: In step (2), the calcination is carried out in an inert atmosphere and an air atmosphere, respectively, the calcination temperature is 450-550° C., the calcination time is 4-6 h, and the air calcination temperature is 240-260° C., and the air calcination time is 4-6 h; Preferably, the inert atmosphere is N2 or Ar.
8. The method for preparing a carbon-based catalyst according to claim 3, characterized in that: Step (3) simulating flue gas removal conditions in a fixed bed reactor to perform desulfurization treatment; Preferably, the sulfidation conditions are: temperature of 110-130° C., gas flow rate of 180-220 mL / min, containing 800-1000 ppm SO2, 0-5 vol% H2O, 8-12 vol% O2, and N2 / Ar as the balance gas.
9. An application of the carbon-based catalyst described in 1 or 2, characterized in that: The carbon-based catalyst is used for the removal and regeneration of dioxins.
10. The use of the carbon-based catalyst according to claim 9, characterized in that: The carbon-based catalyst after dioxin removal is regenerated at 400-500°C in an inert atmosphere for 1-2 hours at a heating rate of 5-10°C / min.
